Altered offspring neurodevelopment in an L-NAME-induced preeclampsia rat model - Nakamura, Noriyuki; Ushida, Takafumi; Onoda, Atsuto; Ueda, Kazuto; Miura, Ryosuke; Suzuki, Toshihiko; Katsuki, Satoru; Mizutani, Hidesuke; Yoshida, Kosuke; Tano, Sho; Iitani, Yukako; Imai, Kenji; et al. (Frontiers in Pediatrics, 2023)
Introduction To investigate the mechanism underlying the increased risk of subsequent neurodevelopmental disorders in children born to mothers with preeclampsia, we evaluated the neurodevelopment of offspring of a preeclampsia rat model induced by the administration of N-nitro-L-arginine methyl ester (L-NAME) and identified unique protein signatures in the offspring cerebrospinal fluid. Methods Pregnant rats received an intraperitoneal injection of L-NAME (250 mg/kg/day) during gestational days 15–20 to establish a preeclampsia model. Behavioral experiments (negative geotaxis, open-field, rotarod treadmill, and active avoidance tests), immunohistochemistry [anti-neuronal nuclei (NeuN) staining in the hippocampal dentate gyrus and cerebral cortex on postnatal day 70], and proteome analysis of the cerebrospinal fluid on postnatal day 5 were performed on male offspring. Results Offspring of the preeclampsia dam exhibited increased growth restriction at birth (52.5%), but showed postnatal catch-up growth on postnatal day 14. Several behavioral abnormalities including motor development and vestibular function (negative geotaxis test: p < 0.01) in the neonatal period; motor coordination and learning skills (rotarod treadmill test: p = 0.01); and memory skills (active avoidance test: p < 0.01) in the juvenile period were observed. NeuN-positive cells in preeclampsia rats were significantly reduced in both the hippocampal dentate gyrus and cerebral cortex (p < 0.01, p < 0.01, respectively). Among the 1270 proteins in the cerebrospinal fluid identified using liquid chromatography-tandem mass spectrometry, 32 were differentially expressed. Principal component analysis showed that most cerebrospinal fluid samples achieved clear separation between preeclampsia and control rats. Pathway analysis revealed that differentially expressed proteins were associated with endoplasmic reticulum translocation, Rab proteins, and ribosomal proteins, which are involved in various nervous system disorders including autism spectrum disorders, schizophrenia, and Alzheimer's disease. Conclusion The offspring of the L-NAME-induced preeclampsia model rats exhibited key features of neurodevelopmental abnormalities on behavioral and pathological examinations similar to humans. We found altered cerebrospinal fluid protein profiling in this preeclampsia rat, and the unique protein signatures related to endoplasmic reticulum translocation, Rab proteins, and ribosomal proteins may be associated with subsequent adverse neurodevelopment in the offspring.